Improving Verbal Communication in Stroke Patients After Lip Exercise and Blowing Pipe Intervention - Suyanto, Suyanto; Kurniawan, Eko; Melastuti, Erna (Media Keperawatan Indonesia, 2025)
Stroke patients frequently experience verbal communication impairments due to orofacial muscle weakness and reduced respiratory control. These conditions significantly affect their quality of life and social interactions. This study aimed to evaluate the effectiveness of lip exercise and blowing pipe interventions in improving verbal communication among stroke patients. A pre-experimental study with a pre-test and post-test design was conducted at a public hospital's inpatient ward. A total of 21 stroke patients were selected using purposive sampling. The intervention group received a structured program of lip exercise and blowing pipe therapy twice daily for 5 days. Verbal communication ability was measured using the Frenchay Dysarthria Assessment (FDA) scale. Data were analyzed using a paired t-test. There was a significant improvement in verbal communication scores in the intervention group (p < 0.05), while no significant changes were observed in the control group. The combined therapy demonstrated effectiveness in enhancing articulation, breath control, and overall verbal expression. Lip exercise and blowing pipe interventions are effective, simple, and low-cost therapies that significantly improve verbal communication in stroke patients.